2019
DOI: 10.3390/molecules24183277
|View full text |Cite
|
Sign up to set email alerts
|

Active Anti-Inflammatory and Hypolipidemic Derivatives of Lorazepam

Abstract: Novel derivatives of some non steroidal anti-inflammatory drugs, as well as of the antioxidants α-lipoic acid, trolox and (E)-3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid with lorazepam were synthesised by a straightforward method at satisfactory to high yields (40%–93%). All the tested derivatives strongly decreased lipidemic indices in rat plasma after Triton induced hyperlipidaemia. They also reduced acute inflammation and a number of them demonstrated lipoxygenase inhibitory activity. Those compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Its high lipophilicity allows it to approach DPPH effectively and interact with it, producing a stable phenolic radical due to the positive inductive effect of the tert -butyl substituents. Lipophilicity seems to be a significant property for interaction with DPPH since BHCA derivatives with high lipophilicity have shown to be effective DPPH reducing agents [ 28 , 31 ]. In contrast, Compound 1 produces a less stable phenolic radical after hydrogen abstraction and thus it could not reduce DPPH effectively even at 200 μΜ.…”
Section: Discussionmentioning
confidence: 99%
“…Its high lipophilicity allows it to approach DPPH effectively and interact with it, producing a stable phenolic radical due to the positive inductive effect of the tert -butyl substituents. Lipophilicity seems to be a significant property for interaction with DPPH since BHCA derivatives with high lipophilicity have shown to be effective DPPH reducing agents [ 28 , 31 ]. In contrast, Compound 1 produces a less stable phenolic radical after hydrogen abstraction and thus it could not reduce DPPH effectively even at 200 μΜ.…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen derivatives 8 and 9 were more active than ketoprofen derivatives 11 and 12 . This may partly be related to the less rigid structure of the former NSAID, since we have shown that rigid molecules seem to offer diminished activity [ 39 , 40 ]. 4-Hydroxy cinnamic acid shows low potency in LOX inhibition; however, compounds bearing this structure or the ( E )-phenyl-propene moiety show considerable activity on LOX inhibition [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final compounds were synthesized by esterification of the above acids with 3,4,5-trimethoxybenzyl alcohol, using DCC in the presence of 4-dimethylaminopyridine (DMAP) ( Scheme 3 and Figure 1 ) [ 17 ] with yields 43–80%. The spectroscopic (IR, 1 H-NMR, 13 C-NMR) studies and chemical analysis (C, H, N) were carried out to characterize the new compounds and support their molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…After 3.5 h, the hind paws were excised and weighed separately. The produced edema was estimated as paw weight increase [ 17 ].…”
Section: Methodsmentioning
confidence: 99%